Synthesis of Alkyl Polyglycoside Surfactants from Tert-butyl Glycosides and Fatty Acids - Pramudono, Bambang (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: It is necessary to develop an environmentally friendly type of alkyl polyglycoside (APG) surfactant; this can be done by making surfactants using raw materials based on carbohydrates and fatty acids. The longer the carbon chain in the fatty acid used, the hydrophilic-lipophilic balance will be smaller so it will be easier in choosing the type of surfactant in its use. Until now, there has been no research on the effect of carbon chain length of fatty acids used in the formation of surfactants against surfactant properties. The effect of carbon fatty chain length on surfactant properties can be studied in the following manner. Preparation of APG surfactants was performed with tert-butyl glycoside and various fatty acids (myristic acid, palmitic acid, and oleic acid) using a para-toluene sulfonic acid catalyst. Results: Here, there are three reactions, with myristic acid forming tert-butyl miristyl glycoside surfactant (TBMG), with palmitic acid formed tert-butyl palmityl glycoside (TBPG), and with oleic acid to form tert-butyl oleyl glycoside (TBOG). The surfactant was tested for use as an emulsifier in the water-xylene emulsion system, then analyzed the percent emulsion stability and hydrophilic-lipophilic balance (HLB). Conclusion: It is found that TBOG is more stable compared to TBPG and TBMG, from HLB values for TBPG and TBOG surfactants are 3.94 and 3.01 so that this surfactant can be used for water-in-oil type emulsifier, for TBMG its HLB value is 11.24 can be used as emulsifier type oil-in-water.